Gender Perspectives in Kasnono Traditional Rituals Speech in Biloto Village, South Central Timor District - Agnes Maria Diana Rafael; Asti Yunita Benu (Fakultas Ilmu Budaya, Universitas Dian Nuswantoro, 2021)
The people of South Central Timor District In East Nusa Tenggara are “archaic” people or traditional people who still maintain their life with local cultural patterns from the legacy of their ancestors. In South Central Timor District, to be precised in Biloto Village, there is a traditional ritual which is a ritual that is cultured for the bride. A bride from any clan and from any tribe is married to one of the Timorese men or atoin meto, she is obliged to follow this Kasnono ritual. If the bride doesn't perform the ritual, then all the bad things will overflow the bride and her new family. This study aims to examine the gender perspective contained in Kasnono's traditional speech and ritual stages. The methods used in studying the data is descriptive qualitative method that used interviews and observation. The method of observation is carried out with the aim of obtaining a complete picture of the data regarding real verbal and nonverbal behavior regarding the continuity of the ritual. Meanwhile, based on the results of observations and interviews, although at a glance this ritual is burdensome for women or wives in their married life, the data proved that the women are the core of their household, whose positions are equal to men, that their roles and existence are highly respected and upheld. In the tradition of Biloto village, a granary is a place of honor for all parts of the Timorese community in the village of Biloto. Therefore, by implementing this ritual the wives hold the key to the family's granary, whereas the husband and the other family members are not allowed to enter the barn.. Finally by carrying out the Kasnono traditional ritual, the wife officially becomes the main control to manage everything in the family house and the wife’s position is equal to her husband..